2010
DOI: 10.1039/c0jm02440f
|View full text |Cite
|
Sign up to set email alerts
|

Individual nanocomposite sheets of chemically reduced graphene oxide and poly(N-vinyl pyrrolidone): preparation and humidity sensing characteristics

Abstract: Individual nanocomposite sheets of chemically reduced graphene oxide (CRG) and poly(N-vinyl pyrrolidone) (PVP), namely CRG/PVP, have been fabricated through a simple one-pot procedure. The structure and composition of the as-prepared CRG/PVP sheets were complementarily characterized using solid-state 13 C NMR, atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and other spectroscopic measurements, demonstrating that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 38 publications
(51 reference statements)
1
39
0
Order By: Relevance
“…In addition, the minimum value of impedance increases, and this is consistent with the mechanism proposed before. M a n u s c r i p t 14 When one side of the GO film was sealed, less water molecules can be absorbed inside the film at the same time, resulting in a slow and low responsible value.…”
Section: Borini Et Al Suggestion a New Equivalent Circuit Instead Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the minimum value of impedance increases, and this is consistent with the mechanism proposed before. M a n u s c r i p t 14 When one side of the GO film was sealed, less water molecules can be absorbed inside the film at the same time, resulting in a slow and low responsible value.…”
Section: Borini Et Al Suggestion a New Equivalent Circuit Instead Ofmentioning
confidence: 99%
“…Recently, both of them have been employed as the materials for humidity sensoring. Guo et al reported an individual nanocomposite sheet of chemically reduced graphene oxide and poly(N-vinyl pyrrolidone) which showed a humidity sensitive electrical conductivity in nanoscale [14]. Similarly, A graphene/polypyrrole composite has been prepared and the humidity sensing properties was measured using a LCR (inductance, capacitance and resistance) analyzer, and the material has humidity sensing properties for relative humidity in the range of 12-90% [15].…”
Section: Introductionmentioning
confidence: 98%
“…Zhang et al [42] have proved that L-AA was an effective reductant to remove the oxygen functionalities on GO surface and recover the electronic conjugation state of reduced GO significantly. L-ascorbic acid (L-AA) (10 times weight of GO sheets, the reductant need not be removed because Zhang et al [43] has proved that the oxidized products of L-AA could act as stabilizer of the reduced GO aqueous suspension) was added under vigorous stirring at 90 C for15 min [44]. Then stored at room temperature for further usage.…”
Section: Preparation Of Pva/nfc/rgo Nanocomposite Filmsmentioning
confidence: 99%
“…24 With the formation of rGO, polyvinylpyrrolidone (PVP) was covalently grafted on the atomically flat surface of rGO. 25, 26 Afterwards, integrin specific ACDCRGDCFCG peptide (RGD4C) molecules were anchored onto the backbone of PVP via hydrogen bonding. 27 The as-prepared RGD-anchored PVP-modified rGO (rGO-PVP-RGD) was used as a nanocarrier for targeted PS chlorin e6 (Ce6) delivery.…”
Section: Introductionmentioning
confidence: 99%